Estimation of Generalized Entropy and Atkinson Inequality Indices from Complex Survey Data - Martin Biewen; Stephen P. Jenkins (Institute for the Study of Labor (IZA), 2003)
Applying a method suggested by Woodruff (1971), we derive the sampling variances of Generalized Entropy and Atkinson inequality indices when estimated from complex survey data. It turns out that this method also greatly simplifies the calculations for the i.i.d. case when compared to previous derivations in the literature. Both cases are illustrated with examples from the German Socio-Economic Panel Study and the British Household Panel Survey.
Keywords: C14; D31; 330; inequality; statistical inference; complex surveys; Disparitätsmaß; Schätztheorie; Schätzung; Theorie; Großbritannien; Deutschland